Peningkatan Keterampilan Menulis Berita Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Siswa Kelas VIII D MTS Pondok Pesantren As-Salam Naga Beralih Kabupaten Kampar - Mardiah, Mardiah (GERAM: Gerakan Aktif Menulis, 2020)
Based oninitial observation the fiel, the student news writing skills MTs Boarding School As-Salam Naga Beralih Kampar regency still low. This isi caused by several factors, one of which is the selection of the learning modeling accuracies. Learning model used is still the main choice in lecture learning. Another factor that comes from the students was the lack of motivation to write the story bacauce it was though that writing astoryisa difficult activity. To correct this condition carried through Classroom Action Research type Jigsaw Cooperative Learning Model. Purpose of this research class action (1) describing the process of improving the student skill in writing news items in class VIII D of class VIII d MTs boarding School As-Salam Naga Beralih Kampar regency increases trough Jigsaw cooperative learning model, and (2) describing the supporting factors improved writing skills class VIII D news MTs Boarding School As-Salam Naga beralih Kampar regency increases trough jigsaw cooperative learning model. Class room Action research was conducted in two cycles. Each cycle through the stages of (1) planning, (2) action, (3) observation, (4) reflection. The subjects were students of class VIII D Boarding School As-Salam Naga Beralih Kampar regency. The results of this study showed on increase in news writing skill class VIII D with respect to completeness of the content of the news (5 w = 1 H), regularity of exposure, use of effective sentences, vocabulary used, the accuracy of using EYD, and attractiveness of headlines along with the formulation of several contributing factors in improving writing news class VIII D boarding School As-Salam Naga Beralih Kampar Regency. Jigsaw cooperative learning model type is suitable for use by teachersin teaching students to writing news. Teachers should choose appropriate learning steps in using the model of cooperative learning Jigsaw type new sin the learning process.